The implementation of risk management and its monitoring through KRI's with a focus on ESG: a narrative review (Research, Society and Development, 2022)
To protect and generate value, organizations adopt Risk Management methodologies to be less prone to the risks inherent to their business, generally using the ISO 31000 guidelines. For the effectiveness of a Risk methodology, however, its monitoring through key risk indicators (KRI's), which expand the understanding of risks, demonstrating the organization's performance in face of them and supporting decision-making. KRI's should be used, above all, in the monitoring of critical risks, such as those related to ESG, an increasingly exponential trend, which demonstrates whether the company generates positive impacts in relation to the three aspects that the term covers: environmental; Social; and governance. However, the academic literature lacks methodologies that cover the themes: risks, KRI's and ESG. Therefore, the objective of the work was to use the concepts of ISO 31000 as a reference and analyze, via a narrative literature review, the implementation of a risk management system, considering its monitoring through KRI's, using with application to the ESG. To this end, a qualitative, exploratory research was carried out, with technical procedures that went through a narrative review of the literature, in which 10 articles were selected for analysis. The results achieved serve to promote discussions and the permeability of the theme in the literature, in addition to acting as a reference for companies regarding Risk Management, KRI's and ESG. In conclusion, the research met its objective and leaves prepositions for future studies.